Spatial distribution of temporal precipitation contrasts in South Africa - Botai, Christina M.; Botai, Joel O.; Adeola, Abiodun M. (South African Journal of Science, 2018)
The focus of the present study was to investigate the spatial-temporal variability and trends of precipitation concentration across South Africa using the Tropical Rainfall Measuring Mission (TRMM) 3B42 version 7 satellite precipitation data sets spanning 1998–2015. In the analysis, the precipitation concentrationindex (PCI) was used to infer the variability of temporal precipitation contrasts and the spatial distributions at annual, seasonal and supra-seasonal timescales. The results indicate that precipitation concentration across South Africa exhibits noticeable spatial-temporal variability. In terms of PCI classification criteria,the precipitation distribution ranges from relatively uniform (mainly in the central and southern interior of South Africa) to highly irregular (especially to the northeastern and western parts of South Africa) at annual timescales. At seasonal timescales, the precipitation distribution is uniform during December–Februaryseason, moderate during March–May and September–November seasons while during the June–August season, the precipitation distribution is highly irregular. Furthermore, during the 1998–2015 period, there exists a spatial and temporal pattern of PCI trends which are generally statistically insignificant. The PCI analysis results reported in this study are essential because they provide valuable information on the longterm total variability in the precipitation records across South Africa. In particular, this study contributes towards evaluating the spatial contrasts or concentration of the different accumulated amounts of thereceived precipitation. Results from this study have important scientific and practical applications in hydrological hazard risks (floods and droughts) and soil erosion monitoring.Significance:• Precipitation concentration exhibits spatial-temporal variability.• At an annual timescale, precipitation concentration is highly irregular in most parts of the country.• Precipitation concentration distribution varies across seasons.